Truly Malaysia! And Sept 16 will say it all - Abd Razak, Dzulkifli (2008)
with the prime minister last Sunday. It was an occasion most of them will remember for a long time because it was a gathering of perpaduan (unity). Every one of the students present wore a multicoloured Tshirt with the word "Perpaduan" emblazoned across it—in Bahasa Malaysia, English, Chinese, and Tamil. If a jawi version and that of the languages of the major ethnic groups in Sabah and Sarawak were also included, it would have been a more complete symbol of unity for Malaysia. After all, there are more than 65 ethnic minorities in Sabah alone!